-3(t-4)+9t=8t-6

Simple and best practice solution for -3(t-4)+9t=8t-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(t-4)+9t=8t-6 equation:


Simplifying
-3(t + -4) + 9t = 8t + -6

Reorder the terms:
-3(-4 + t) + 9t = 8t + -6
(-4 * -3 + t * -3) + 9t = 8t + -6
(12 + -3t) + 9t = 8t + -6

Combine like terms: -3t + 9t = 6t
12 + 6t = 8t + -6

Reorder the terms:
12 + 6t = -6 + 8t

Solving
12 + 6t = -6 + 8t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-8t' to each side of the equation.
12 + 6t + -8t = -6 + 8t + -8t

Combine like terms: 6t + -8t = -2t
12 + -2t = -6 + 8t + -8t

Combine like terms: 8t + -8t = 0
12 + -2t = -6 + 0
12 + -2t = -6

Add '-12' to each side of the equation.
12 + -12 + -2t = -6 + -12

Combine like terms: 12 + -12 = 0
0 + -2t = -6 + -12
-2t = -6 + -12

Combine like terms: -6 + -12 = -18
-2t = -18

Divide each side by '-2'.
t = 9

Simplifying
t = 9

See similar equations:

| 60y^2+3y-36=0 | | x^2=14-7x | | 5(x-8)+26= | | 5x-4(4x-1)=2 | | -6x-142=2x+98 | | 5x+45+9x=180 | | 17=64-n | | i7n/9-62=5n/9-49 | | 31x=56 | | Y/3-4=-2 | | B/5-2=2 | | 4+-6+9=x | | .10x+12y=2990 | | a/4-b/3=5/12 | | -2+5n+3n^2=0 | | 10=30/z | | 9p-19=5(p-2)-2(7-2p) | | 5v-5v+v=16 | | Y=-4(6)-10 | | (14-2x)+40=180 | | -2x-10=-2x-10 | | x-10y=13 | | 1=k/10-1 | | x^2-14x-40= | | (14-2x)+40=90 | | 12x+6y= | | 2(-6p+7)+4(p+3)= | | 3x^2-20x+25= | | 11d-4d-3d+d-4d=12 | | 23-4r=3 | | -48-3x=42+2x | | 6X9-/5X |

Equations solver categories